Computational fluid dynamics simulations of wind-driven rain on a mid-rise residential building with various types of facade details. Issue 2 (4th March 2017) - Kubilay, A.; Carmeliet, J.; Derome, D.
Abstract : Numerical studies of wind-driven rain (WDR), reporting detailed analysis of rain exposure on building facades, focus mainly on simplified building facades. However, small-scale facade details have a large impact on the rain exposure of a building, redistributing WDR locally. The present study reports results of computational fluid dynamics simulations with Eulerian multiphase (EM) model for WDR on a stand-alone mid-rise residential building. The influence of facade details, namely roof overhangs, balconies and window sills, is analysed. It is shown that even a very small surface detail, such as a window sill with a size of 0.10 m, can decrease catch ratio by up to 37% and droplet impact speed by up to 40%. Numerical simulations also show the practicality of the EM model for detailed analysis of WDR intensity on a complex building and its ability to be used as a design tool.